Ventajas y desventajas de la firma de tratados de libre comercio (Estudios) - Jaramillo Vásquez, Santiago José (2023)
The motive behind this study was to examine the various contradictions in the scientific community regarding earnings or losses caused by entering Free Trade Agreements (FTAs). As no similar studies on this topic have been made in recent years, this study was highly necessary. The main objective of the study was to analyze the theory presented by the authors regarding the advantages and disadvantages in entering a FTA. A literature review helped narrow down 44 scientific sources from years 2016 to 2021 in Scopus, Scielo, Sage and Redalyc. The results revealed that industrialized countries are the ones which generally received greater advantages in regard to free trade while non-industrialized countries had considerable disadvantages at the time of entering a FTA. It was found that FTAs may bring both benefits and losses depending on the context of a country; it is very important to learn to use this tool properly.